Observational study of peripheral retinal degenerations in normal population in Sarojini Devi eye hospital. - Dr.Ch.Srinivasa M, Dr.M.Kavitha Jyothi, (International Journal of Scientific Research and Management (IJSRM), 2017)
The study of retinal periphery has a significance in clinical evaluation of an eye. By virtue of it's peculiar characteristics it is prone for certain lesions, and some of them could be pathological. The study by various workers indicates the varied type of pathological lesions residing in the retinal periphery. Various lesions found in this region in supposedly normal persons like paving stone degeneration, Lattice degeneration, cystoid degeneration, white with pressure and white without pressure areas are likely to be missed by routine examination. unless specifically looked for